Financial development and real exchange rate misalignments effects on environmental pollution - Xiao, Lin; Ahmad, Muneeb; Waseem, Liaqat Ali; Ahmad, Muhammad Munir; Khan, Ashfak Ahmad (Frontiers in Environmental Science, 2022)
The research looked at the influence of the real exchange rate mismatch and LDCs' financial development on CO2 emissions in Asian countries. The study applied to the panel data from 1970 to 2021. The research data was tested using ARDL bound testing and PMG/ARDL estimators with dynamic OLS estimators. The results reveal that the long-term real exchange rates for LDCs are expected to increase CO2 emissions in Asian countries with improved trade and net foreign asset positions. Relative productivity and trade openness also increase the exchange rate, so it also plays an important role in the growth of CO2 emissions. According to the panel's estimates, the long-term financial growth of LDCs would be enhanced by a rise in real investment and human capital. Except for Egypt, all LDC currencies are overpriced throughout the research period. At the same time, they would be harmed by increased openness, net foreign assistance inflows, and currency misalignment. Overvaluation harms Bahrain's financial growth, while undervaluation helps Egypt's, and is an exception to the rule that currency misalignment does not affect financial growth in any of the LDCs over the long term. In the medium term, more real investment, human capital, and official assistance inflows would enhance financial growth in Qatar, Bahrain, Singapore, and South Korea. In contrast, trade openness would slow it down in Egypt and Kuwait.